Chemical composition of ferromanganese nodules and crusts from the Pacific using wet chemistry - D Pasho (PANGAEA, 2023)
Manganese nodules were retrieved during various cruises of the R/V Vema and R/V Robert Conrad from Lamont Doherty Earth Observatory (LDEO). Their chemical composition was determined using standard wet chemistry procedures.